Association of BoLA-DRB3 Alleles with the Progression of Bovine Leukosis in the Lucerna Breed - Hernández-Herrera, D. Y.; Carrillo-González, D. F. (Tropical Animal Science Journal, 2024)
The bovine leukosis virus causes enzootic bovine leukosis (BLV) of the Retroviridae family and is the most significant neoplastic disease in cattle, leading to substantial economic losses globally. This study aimed to associate the progression of bovine leukosis with BoLA-DRB3 alleles in the Lucerna breed. A total of 104 animals were tested for the presence of BLV by nested PCR, the development of persistent lymphocytosis (PL) by peripheral blood smear, antibody titers (AT) to BLV by ELISA, and proviral load (PVL) by qPCR. Animals were genotyped for the BoLA-DRB3 gene by PCR-SBT. Allele frequencies of the DRB3 gene were estimated and associated using Fisher’s exact test and odds ratio. About 93.2% of the animals were virus positive, and 18.3% developed PL. Fifty percent of the animals had elevated AT with a value of 88.7 log2, and 43.3% had elevated PVL with 326871 copies/105 cells. In total, 17 BoLA-DRB3 alleles were found; the BoLA-DRB3*011:01 allele (12.1%) was the most frequent. Two alleles showed an association with susceptibility to viral infection (BoLA-DRB3*15:01 and *23:01), and only the BoLA-DRB3*38:01 allele was considered resistant. The BoLA-DRB3*11:01 and *15:01 alleles were not associated with LP, and neither allele was associated with high LP. Low AT was found in the BoLA-DRB3*13:01 and *20:01:02 alleles. The BoLA-DRB3*15:01 and *16:01 alleles were associated with high AT. Low PVL was associated with the BoLA-DRB3*11:01 and *23:01 alleles. BoLA-DRB3*15:01 allele was associated with high PVL. In conclusion, the Lucerne breed has a slow progression of enzootic bovine leukosis.